Celebrity fashion brand endorsement in Facebook viral marketing and social commerce: Interactive effects of social identification, materialism, fashion involvement, and opinion leadership. Issue 1 (7th August 2018) - Jin, Seunga Venus; Ryu, Ehri
Abstract : Purpose: In light of Facebook-based viral marketing and social commerce, the purpose of this paper is to test the moderating role of social identification with the Facebook profile owner (celebrity as aspirational reference group vs ingroup member (college student, same school) vs outgroup member (college student, different school)) in Facebook-based fashion brand marketing and management. Design/methodology/approach: A randomized between-subjects experiment (celebrity's Facebook profile vs ingroup member's Facebook profile vs outgroup member's Facebook profile vs control condition, n =73) was conducted. The sample was composed of college students recruited from a subject pool in a US university. Findings: Results of multiple regression analyses indicate that social identification with the Facebook profile owner and ingroup vs outgroup perception moderate the influence of consumers' materialism, fashion involvement and opinion leadership on interpersonal attraction to the celebrity, wishful identification with the celebrity, emotional quotient, involvement with the ads, advertising believability and willingness to buy the advertised fashion products. Furthermore, the results of structural equation modeling analyses show that source credibility perception (both the celebrity who endorses her own brand and the Facebook profile owner) mediates the relationship between experimental conditions (celebrity as aspirational outgroup vs same school student as an ingroup member vs different school student as an outgroup member) and the outcome variables (interpersonal attraction to the celebrity, involvement with ads, and advertising believability) in viral marketing leveraging a social media platform. Originality/value: This study makes several theoretical contributions to consumer psychology and provides managerial implications for Facebook-based fashion marketing and fashion brand management.